Co-designing innovative cropping systems with stakeholders - Marraccini, Elisa; Silvestri, Nicola; Ingram, Julie (Italian Journal of Agronomy, 2024)
Over the last decades, farmers have been subject to the impacts of a number of driving forces acting at the global level, which have substantially modified the structure and the organization of cropping systems [...].